Immediate prepectoral implant reconstruction using TiLOOP Bra Pocket results in improved patient satisfaction over dual plane reconstruction. Issue 4 (26th February 2021) - Ng, E‐Ern Ian; Quah, Gaik Si; Graham, Susannah; Kanesalingam, Kavitha; Meybodi, Farid; Hsu, Jeremy; Elder, Elisabeth E.; French, James
Abstract: Background: Implant‐based reconstruction accounts for the majority of breast reconstructive procedures performed in Australia. More recently, immediate prepectoral implant reconstruction using the TiLOOP Bra Pocket has gained popularity. This study compares post‐surgical complications and patient‐reported quality of life outcomes between immediate prepectoral and dual plane implant reconstruction. Methods: A retrospective study of 80 consecutive patients who underwent nipple‐sparing mastectomies and immediate implant reconstruction was conducted. Implants were either completely covered with TiLOOP Bra and/or TiLOOP Bra Pocket (pfm medical, Cologne, Germany) and secured in the prepectoral space (prepectoral group) or placed in the subpectoral plane with inferolateral mesh coverage (dual plane group). Data surrounding patient demographics, clinical details and post‐surgical outcomes were compared. Patient‐related quality of life outcomes were assessed with the Breast‐Q questionnaire. Results: A total of 80 patients (109 breasts) operated on between June 2016 and December 2018 were included. The prepectoral and dual plane groups comprised of 40 patients each, including 50 and 59 operated breasts, respectively. Post‐operative complications were comparable with 11 (22%) overall complications in the prepectoral group and eight (14%) in the dual plane group ( P = 0.313). Implant loss was uncommon with four (8%) cases in the prepectoral group and five (8.5%) in the dual plane group ( P = 0.929). Patient‐reported quality of life outcomes were superior after prepectoral reconstruction with patients reporting a significantly higher score in the satisfaction with breasts domain (68.9 versus 57.5; P = 0.036). Conclusion: Immediate prepectoral implant reconstruction with the TiLOOP Bra Pocket was associated with improved patient satisfaction and demonstrated no difference in early post‐operative outcomes. Abstract : Immediate prepectoral implant reconstruction with the TiLOOP Bra Pocket was associated with improved patient satisfaction and demonstrated no difference in early post‐operative outcomes when compared to dual plane reconstruction.